Kesenian Melayu Islam : Jiwa Islam Dalam Pengkaryaan. - Nik Hassan Shuhaimi Nik Abd. Rahman; Zuliskandar Ramli; Othman Md. Yatim; Ros Mahwati Ahmad Zakaria (2005)
Malay Islamic arts will focus on the concept of Islamic arts and who is Islamic Malay and also the creation of arts. Generally, arts is regarded as human creation and contains the expression of the artists, and all types of decorative motifs will take into consideration their functions. Among the aspects of arts are calligraphy, architecture, textile, pottery, theatre, dance, music, self-defence and etc. To create art, a creator must posses the ability, professionalism, creative power, artistic ideas and knowledge about nature and life. The meaning and the position of Islamic arts discussed by Islamic scholars define Islamic arts from the aspects of types, shapes, themes, sources, origin, typology, date of creations, and the creator in terms of origin, and development. Islamic arts discussed are arts created in Malaysia by the Islamic Malays. Islamic Malays speak Malay language, practice Malay adat and traditions and a Muslim. In this context, ethnicity is not taken into account in defining whether an individual is a Malay or non-Malay but a Muslim Islamic arts consist of visual arts and non-visual arts including songs, zikir and etc. It can be defined as the arts that create tauhid and Islamic thoughts and never copy Allah’s creation and aware of what.